A Distributed Agents QoS Routing Algorithm to Transmit Electrical Power Measuring Information in Last Mile Access Wireless Sensor Networks. (2nd November 2013) - Yang, Ting; Xiang, Wenping; Ye, Linqi
Internet of Things or wireless sensor networks (WSNs) can be utilized in monitoring electrical power consumption. For electrical power application, the main issue is how to effectively apply self-organized WSNs technology to handle the last mile communication and supply the reliable, real-time transmission. For example, great number of renewable generators' instantaneous voltage and power parameters should be reported in real time to dispatching center, which is the primary guarantee to keep the power system's stability. In this paper, integrating traffic engineering and distributed agent technologies, a novel distributed agents QoS routing algorithm is proposed to transmit electrical information flows with multi-QoS constraints. The algorithm can explore fast forward path with multiagents and guarantee transmitting quality with smooth allocating different traffic. We also present the mathematical analysis to prove the algorithm's validity. Finally, in the computer simulation, the average end-to-end delay, routing overhead, and links' bandwidth occupation ratio are computed to evaluate the algorithm performance. Coincident results show that the new algorithm can provide short end-to-end transmission with optimal utilized communication resource. A health infrastructure with load balance can effectively avoid the potential congestion and has robust capability to bear abrupt strong traffic flows.